Large animal induced pluripotent stem cells as pre-clinical models for studying human disease - Plews, Jordan R (Blackwell Publishing Ltd, 2012)
The derivation of human embryonic stem cells and subsequently human induced pluripotent stem cells (iPSCs) has energized regenerative medicine research and enabled seemingly limitless applications. Although small animal models, such as mouse models, have played an important role in the progression of the field, typically, they are poor representations of the human disease phenotype. As an alternative, large animal models should be explored as a potentially better approach for clinical translation of cellular therapies. However, only fragmented information regarding the derivation, characterization and clinical usefulness of pluripotent large animal cells is currently available. Here, we briefly review the latest advances regarding the derivation and use of large animal iPSCs.